2023
DOI: 10.1172/jci.insight.166012
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine storm–based mechanisms for extrapulmonary manifestations of SARS-CoV-2 infection

Abstract: Viral illnesses like SARS-CoV-2 have pathologic effects on non-respiratory organs in the absence of direct viral infection. We injected mice with cocktails of rodent equivalents of human cytokine storms resulting from SARS-CoV-2 / COVID-19 or Rhinovirus common cold infection. At low doses, COVID-19 cocktails induced glomerular injury and albuminuria in Zhx2 hypomorph and Zhx2 +/+ mice to mimic COVID-19 related proteinuria. Common Cold cocktail induced albuminuria selectively in Zhx2 hypomorph mice to model rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…SARS-Cov-2 infection activates the body's immune response and causes disorders of the immune system like cytokine storm which induces whole-body manifestations and makes it difficult to treat severe cases of COVID-19. 73 Although OA was not defined as an immune-related disease and was different from RA traditionally, recent studies demonstrated that the immune reaction was involved in OA pathogenesis, and this was also confirmed by elevated levels of immunoglobulin and complement in the synovial fluid of the joints in patients with OA. 74,75 In this study, immune infiltration levels of COVID-19 and OA were evaluated by CIBERSORT, and the results showed that Macrophages were increased while NK cells and Mast cells were decreased in both these two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-Cov-2 infection activates the body's immune response and causes disorders of the immune system like cytokine storm which induces whole-body manifestations and makes it difficult to treat severe cases of COVID-19. 73 Although OA was not defined as an immune-related disease and was different from RA traditionally, recent studies demonstrated that the immune reaction was involved in OA pathogenesis, and this was also confirmed by elevated levels of immunoglobulin and complement in the synovial fluid of the joints in patients with OA. 74,75 In this study, immune infiltration levels of COVID-19 and OA were evaluated by CIBERSORT, and the results showed that Macrophages were increased while NK cells and Mast cells were decreased in both these two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation studies using whole glomerular protein extracts showed the interaction of ZHX proteins with APA (podocyte body) and ephrin B1 (slit diaphragm) ( 8 ), suggesting that ZHX1-ZHX2 and ZHX2-ZHX3 heterodimers are tethered to the cytoplasmic domains of these proteins, respectively. Absence of APA or ephrin B1 or reduced expression of ZHX2 (BALB/cJ mice or Zhx2 flox/flox -NPHS2 promoter Cre +/+ mice) alters the proteinuria profile and suggests the presence of alternative transmembrane-binding partners ( 8 ), one of which is IL-4Rα ( 6 ), the receptor for IL-4 and IL-13 in podocytes. In proteinuric conditions, loss of heterodimerization of ZHX proteins induced migration of peripherally expressed proteins into the nucleus ( 7 , 14 ).…”
Section: Zhx-angptl4 Pathwaymentioning
confidence: 99%
“…BALB/cJ mice develop more severe adriamycin nephrosis (FSGS model), and anti-APA antibodies induced Angptl4 upregulation only in BALB/cJ mice, which also develop significantly higher albuminuria than BALB/c mice ( 8 ). Only BALB/cJ and Zhx2 flox/flox -NPHS2 promoter Cre +/+ mice develop albuminuria when injected with a common cold cytokine cocktail (model of MCD relapse) ( 6 ). In contrast, beyond a specific threshold of podocyte-specific Zhx2 overexpression in a cell membrane distribution, NPHS2 promoter- Zhx2 transgenic rats injected with adriamycin developed the collapsing variant of FSGS, with high podocyte nuclear ZHX2 expression ( 8 ).…”
Section: Zhx-angptl4 Pathwaymentioning
confidence: 99%
See 2 more Smart Citations